2007
DOI: 10.4141/p06-026
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of cool- and warm-season annual cereal species for winter grazing in Saskatchewan

Abstract: S. M. 2007. The Suitability of cool-and warm-season annual cereal species for winter grazing in Saskatchewan. Can. J. Plant Sci. 87: 739-752. Winter grazing is a practice that can reduce feeding cost for cattle production. Current production has been utilizing traditional cool-season cereals for winter grazing. Warmseason (C 4 ) cereals also have the potential to be adapted to winter grazing in Saskatchewan. The objective of this study was to evaluate cool and warm season annual cereal species for adaptation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 4 publications
2
21
1
2
Order By: Relevance
“…Planting date had no consistent effect on nutritive value at time of harvest. May et al (2007) in Saskatchewan also found DM yield decrease in oat and barley with later seeding dates (mid-May vs. mid-June). The major implication was late planting reduced yield and increased the cost of digestible DM production.…”
Section: Dry Matter Forage Yield Ofmentioning
confidence: 96%
See 2 more Smart Citations
“…Planting date had no consistent effect on nutritive value at time of harvest. May et al (2007) in Saskatchewan also found DM yield decrease in oat and barley with later seeding dates (mid-May vs. mid-June). The major implication was late planting reduced yield and increased the cost of digestible DM production.…”
Section: Dry Matter Forage Yield Ofmentioning
confidence: 96%
“…Increased seeding rates (Walton 1975), DM yield (Berkenkamp and Meeres 1987), and effect of seeding date (May et al 2007) had no effect on CP concentration. Delayed harvest decreased CP yield ha…”
Section: Nutritive Value Of Spring Cerealsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corn (Zea mays L.) as a winter grazing crop for beef cattle has been more limited to the southern areas of eastern Canada, or southern areas of the prairies. Corn is a warm season annual, usually seeded late with variation in the date of maturity depending on the geographic location and available corn heat units (CHU) (May et al, 2007). However, early seeding of late maturing hybrids of corn has immense potential for use in extensive winter grazing systems (Saskatchewan Ministry of Agriculture [SMA], 2008).…”
Section: Introductionmentioning
confidence: 99%
“…İkinci yılda ise vejetatif gelişme periyodu daha uzun olmuş, bitkiler daha fazla boylanmış ve ot verimleri daha yüksek bulunmuştur. Kanada'da kum darı, cin darı, yulaf ve arpa ile çalışan May et al (2007) Hassan et al (2000), değişik dozlarda azotlu gübre uygulanan cin darıda en yüksek bitki boyunu 4.5 kg N da -1 uygulamasında belirlemiş, yüksek azot dozunda bitki boyu artışı olmamıştır. Turgut et al (2006) da bu bitkide en yüksek bitki boyunu 6 kg N da -1 dozunda belirlenmişlerdir (66.6 cm).…”
Section: Materyal Ve Yöntemunclassified